Childhood trauma and problematic internet use: A meta-analysis based on students in mainland China - Wang, Xiaotong; Li, Dexian; Li, Shunyu (Frontiers in Psychology, 2023)
Background In recent years, the relationship between childhood trauma and problematic Internet use has been widely studied by scholars, but the research conclusions on the relationship between them are not consistent. Some studies report that childhood trauma and problematic Internet use are significantly correlated. However, others believe that there is a weak correlation between them. So the relationship between them needs to be studied further. The aim of this study is to explore the relationship between childhood trauma and problematic Internet use, and the effects of some moderating variables on both for students in Mainland China. Methods This study followed the requirements of Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statement for literature screening. We searched the related studies on childhood trauma and problematic Internet use in Mainland China from January 2009 to November 2022 from CNKI, Wanfang Data, Chongqing VIP Information Co., Ltd. (VIP), Baidu scholar, ProQuest dissertations, SAGE Online Journals, Elsevier SDOL, Taylor & Francis, Springer, Web of Science, Google Scholar, EBSCO, Medline, Scopus Database, PubMed Central, Embase, The Cochrane Library, PsycINFO, CMA 3.0 was used to analyse the overall effect and test the moderating effect. Results Among the papers included in the meta-analysis in this study, 31 papers reflected the relationship between childhood trauma and problematic Internet use, involving 52,503 subjects, and the sample size ranged from 388 to 16,130. This relationship between childhood trauma and problematic Internet use can be considered as a moderate correlation (r = 0.281, 95%CI[0.221, 0.338], p < 0.001). The results showed that the relationship between childhood trauma and problematic Internet use was affected by different problematic Internet use measures. Meanwhile, meta-regression demonstrated that the relationship between childhood trauma and problematic Internet use was moderated by survey’s year. Specifically, the correlation coefficient between childhood trauma and problematic Internet use also increases with increasing year. However, the relationship between childhood trauma and problematic Internet use was not affected by the region, grade, childhood trauma measures, publication source. Conclusion Childhood trauma is closely related to problematic Internet use. In order to reduce problematic Internet use, corresponding prevention and intervention measures should be taken.